High-wear-resistance polyethylene glycol terephthalate composite material and preparation method thereof
By introducing CNT-PDMS-NH2 hybrids and multifunctional compounds into PET composites, strong interface interactions are constructed, and the problem of poor wear resistance of PET composites under high wear resistance conditions is solved, and PET composites with high wear resistance and high mechanical properties are achieved.
Patent Information
- Application Number
- CN202411951789.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-25
AI Technical Summary
The existing PET composite materials have poor wear resistance under high wear resistance and are difficult to meet the requirements in practical applications.
The CNT-PDMS-NH2 hybrid was obtained by reacting carbon chloride nanotubes with terminal amino polydimethylsiloxane, and the addition reaction between the multifunctional anhydride compound and the multifunctional epoxy compound and the CNT-PDMS-NH2 hybrid and the active end groups of PET was constructed to construct a strong interface interaction and achieve good dispersion of CNT-PDMS-NH2 in PET.
The wear resistance and mechanical properties of PET composite materials are significantly improved, with wear amounts less than 0.090g and tensile strength exceeding 72.00MPa, which can meet the requirements of high and stringent working conditions.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of engineering plastics, and in particular to a highly wear-resistant polyethylene terephthalate composite material and a preparation method thereof. Background Art
[0002] Polyethylene terephthalate (PET), commonly known as polyester resin, is a crystalline saturated polyester obtained by ester exchange of dimethyl terephthalate with ethylene glycol or esterification of terephthalic acid with ethylene glycol to synthesize dihydroxyethyl terephthalate, and then polycondensation reaction. It is the most important variety of thermoplastic polyester, with good crystallization performance, crystallinity of up to 40-60%, outstanding mechanical properties, creep resistance and solvent resistance, excellent physical and mechanical properties in a wide temperature range, long-term use temperature up to 120°C, and excellent transparency and insulation performance. It is widely used as fiber, film, polyester bottle and engineering plastics. However, the application of PET under extreme working conditions with high requirements for wear resistance is still greatly limited.
[0003] Compounding materials with excellent wear resistance with PET is the main means to improve its wear resistance. For example, patent application 202410687318.5 discloses the use of alkaline solution to pre-treat highly wear-resistant nanodiamonds, and in-situ generation of magnesium oxide particles on their surface to improve the mechanical and wear resistance of the composite material; at the same time, mercaptosuccinic acid is introduced into the interior of carbon nanotubes to react with eugenol to improve its compatibility in organic systems, and finally the modified diamonds and carbon nanotubes are melt-extruded with a PET matrix to obtain a high-strength and wear-resistant PET composite material. Patent application 202310399639.0 discloses a modified wear-resistant agent obtained by modifying molybdenum disulfide / manganese dioxide with isopropyl palmitate / tetradecyl dimethylbenzyl ammonium chloride, and compounding it with a PET resin matrix to obtain a PET composite material with wear-resistant properties. However, in the above scheme, the low-polarity anti-wear material is easy to agglomerate in the PET matrix. Even if the anti-wear material is subjected to a simple surface treatment, it is still difficult to solve the interface problem between the anti-wear material and the resin matrix, resulting in its friction reduction effect not being fully exerted and unable to meet the requirements of PET in actual applications under high wear-resistant conditions. Summary of the invention
[0004] The technical problem to be solved by the present invention is that the current PET composite material has poor wear resistance and is difficult to adapt to high wear resistance conditions. To this end, the present invention provides a high wear-resistant polyethylene terephthalate composite material and a preparation method thereof, utilizing the excellent wear resistance of carbon nanotubes (CNT) and the high lubricity of polydimethylsiloxane (PDMS), and obtaining CNT-PDMS-NH with wear-resistant and self-lubricating properties by reacting acyl chloride carbon nanotubes with amino-terminated polydimethylsiloxane. 2Hybrids; further utilizing multifunctional anhydride compounds / multifunctional epoxy compounds and CNT-PDMS-NH 2 The addition reaction of the active amino group of the hybrid / the active end group of PET was used to construct CNT-PDMS-NH 2 The strong interface interaction with the PET matrix enables good dispersion in PET and exerts its anti-wear effect. At the same time, the efficient chain extension of the multifunctional anhydride compound and the multifunctional epoxy compound can greatly increase the molecular weight and molecular entanglement of PET, and obtain a highly wear-resistant PET composite material, which has good application prospects in wear-resistant working conditions.
[0005] The technical solution of the present invention is as follows:
[0006] A highly wear-resistant polyethylene terephthalate composite material comprises the following components in parts by weight:
[0007] 100 parts PET resin, 0.1 to 5 parts CNT-PDMS-NH 2 hybrid, 0.05 to 5 parts of a multifunctional epoxy compound, 0.05 to 5 parts of a multifunctional acid anhydride compound, and 0.01 to 3 parts of an antioxidant; the CNT-PDMS-NH 2 The hybrid is obtained by reacting carbon nanotubes with amino-terminated polydimethylsiloxane.
[0008] Its further technical solution is that the CNT-PDMS-NH 2 The preparation method of the hybrid is as follows: 1 to 20 parts by weight of acyl chloride carbon nanotubes, 1 to 20 parts by weight of a bisamino polydimethylsiloxane mixed compound, and 0.5 to 5 parts by weight of triethylamine are uniformly dispersed in 100 parts of a solvent, reacted at 35 to 100° C. for 5 to 20 hours, and the product is washed and dried to obtain CNT-PDMS-NH 2 Hybrid.
[0009] A further technical solution is that the preparation method of the chlorinated carbon nanotubes is as follows: 0.4 to 5 parts by weight of carboxylated carbon nanotubes are ultrasonically dispersed in 100 parts of thionyl chloride, and refluxed at 60 to 90° C. for 10 to 20 hours to obtain chlorinated carbon nanotubes.
[0010] A further technical solution is that the solvent is selected from at least one of n-hexane, petroleum ether, chloroform, carbon tetrachloride, benzene, toluene and ethyl acetate.
[0011] A further technical solution is that the bis-amino dimethicone compound is selected from one or more of bis-aminopropyl dimethicone, bis-amino PEG / PPG-41 / 3 aminoethyl PG-propyl dimethicone, double-terminated amino dimethicone (and) octylphenol polyether-40 (and) isolauryl alcohol, bis-aminopropyl dimethicone (and) trideceth-10, double-terminated amino dimethicone (and) trideceth-10 (and) stearyl.
[0012] A further technical solution is that the multifunctional epoxy compound is selected from one or more of ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, pentaerythritol tetraglycidyl ether, bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether, resorcinol diglycidyl ether, trimethylolpropane triglycidyl ether, glycerol triglycidyl ether, 1,4-butanediol diglycidyl ether, and castor oil triglycidyl ether.
[0013] A further technical solution is that the multifunctional acid anhydride compound is selected from one or more of pyromellitic anhydride, biphenyltetracarboxylic anhydride, pyromellitic anhydride, maleic anhydride, 1,2,4-tricarboxylic anhydride, 4,4'-oxydiphthalic anhydride, 3,3',4,4'-diphenyl ether tetracarboxylic anhydride, 3,3',4,4'-benzophenone tetracarboxylic anhydride and 3,4,9,10-tetracarboxylic anhydride.
[0014] The further technical scheme is that the antioxidant is selected from β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, di-tert-butyl-p-cresol, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanuric acid, N,N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl] hydrazine, bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite, 4,4'-methylenebis( One or more of: 1,2-di-tert-butylphenol, 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, 2,6-di-tert-butyl-4-(dimethylaminomethyl)phenol, tris[2,4-di-tert-butylphenyl]phosphite, N,N'-bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hexanediamine, 2,6-di-tert-butyl-4-methylphenol and triethylene glycol bis-3-(3-tert-butyl-4-hydroxy-5-methylbenzyl)propionate.
[0015] A further technical solution is that the wear loss of the highly wear-resistant polyethylene terephthalate composite material is less than 0.090 g and the tensile strength exceeds 72.00 MPa.
[0016] The present invention also provides a method for preparing a highly wear-resistant polyethylene terephthalate composite material, comprising the following steps:
[0017] 100 parts by weight of PET resin, 0.1 to 5 parts by weight of CNT-PDMS-NH 2 The hybrid, 0.05-5 parts of a multifunctional epoxy compound, 0.05-5 parts of a multifunctional acid anhydride compound, and 0.01-3 parts of an antioxidant are added into an internal mixer, reacted at 230-260° C. for 10-50 minutes, and the rotor speed is 10-50 r / min to obtain a highly wear-resistant PET composite material;
[0018] The CNT-PDMS-NH 2 The hybrid is obtained by reacting carbon nanotubes with amino-terminated polydimethylsiloxane.
[0019] Compared with the prior art, the technical effects achieved by the present invention include:
[0020] The highly wear-resistant polyethylene terephthalate composite material provided by the present invention comprises CNT-PDMS-NH 2 Hybrid, the CNT-PDMS-NH 2 The hybrid is obtained by reacting carbon nanotubes with amino-terminated polydimethylsiloxane, which has both the excellent wear resistance of carbon nanotubes and the high lubricity of polydimethylsiloxane (PDMS). 2 The addition of hybrids helps to improve the wear resistance of the composite materials.
[0021] Furthermore, the present invention uses multifunctional anhydride compounds and multifunctional epoxy compounds as bridge molecules, and utilizes their active anhydride / epoxy groups to bond with CNT-PDMS-NH 2 The addition reaction of the amino group of the hybrid and the active end group of PET was used to construct CNT-PDMS-NH 2 Strong interfacial interaction with PET matrix enables CNT-PDMS-NH 2 Good dispersion in the PET matrix helps to fully exert the role of efficient wear-resistant self-lubricating.
[0022] Furthermore, the present invention converts CNT-PDMS-NH 2 While the hybrid is connected to the PET matrix, a large number of long-chain branched structures are introduced into the PET molecular chain through the efficient chain extension effect of multifunctional anhydride compounds and multifunctional epoxy compounds, which can greatly increase the molecular weight and molecular entanglement of PET, and further enhance the mechanical strength and wear resistance of the composite material.
[0023] The highly wear-resistant polyethylene terephthalate composite material provided by the present invention comprises a multifunctional epoxy compound, a multifunctional acid anhydride compound and a CNT-PDMS-NH2 Under the joint action of hybrids and other raw materials, the PET matrix is modified, and the obtained polyethylene terephthalate composite material has excellent wear resistance and mechanical properties. After measurement, its wear loss is less than 0.090g and its tensile strength exceeds 72.00MPa, which can meet the performance requirements of materials under highly harsh working conditions. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments are described clearly and completely below. Obviously, the embodiments described below are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.
[0026] It should also be understood that the terms used in this description of the embodiments of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the embodiments of the present invention. As used in the description of the embodiments of the present invention and the appended claims, unless the context clearly indicates otherwise, the singular forms of "a", "an" and "the" are intended to include plural forms.
[0027] Unless otherwise specified, "parts" in the following examples refer to "parts by weight".
[0028] Example 1
[0029] This embodiment provides a highly wear-resistant polyethylene terephthalate composite material and a preparation method thereof.
[0030] The details are as follows:
[0031] Acylation of carbon nanotubes: 2 parts of carboxylated carbon nanotubes were ultrasonically dispersed in 100 parts of thionyl chloride and refluxed at 60° C. for 10 h to obtain acylated carbon nanotubes.
[0032] Preparation of CNT-PDMS-NH 2 Hybrid: 5 parts of acyl chloride carbon nanotubes, 5 parts of bis-aminopropyl polydimethylsiloxane and a mixture of bis-amino PEG / PPG-41 / 3 aminoethyl PG-propyl polydimethylsiloxane (the mass ratio of the two is 1:1), and 1.5 parts of triethylamine are uniformly dispersed in 100 parts of n-hexane, reacted at 50°C for 8h, and the product is washed and dried to obtain CNT-PDMS-NH2 Hybrid.
[0033] Preparation of polyethylene terephthalate composite material: 100 parts of PET resin particles, 2 parts of CNT-PDMS-NH 2 The hybrid, 1.5 parts of ethylene glycol diglycidyl ether, 2 parts of pyromellitic dianhydride, and 0.5 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate were added into an internal mixer, reacted at 230° C. for 20 min, with a rotor speed of 20 r / min, to obtain a highly wear-resistant PET composite material.
[0034] Example 2
[0035] This embodiment provides a highly wear-resistant polyethylene terephthalate composite material and a preparation method thereof.
[0036] The details are as follows:
[0037] Acylation of carbon nanotubes: 2.5 parts of carboxylated carbon nanotubes were ultrasonically dispersed in 100 parts of thionyl chloride and refluxed at 70° C. for 15 h to obtain acylated carbon nanotubes.
[0038] Preparation of CNT-PDMS-NH 2 Hybrid: 10 parts of acyl chloride carbon nanotubes, 10 parts of bisamino PEG / PPG-41 / 3 aminoethyl PG-propyl polydimethylsiloxane, and 1.3 parts of triethylamine were uniformly dispersed in 100 parts of ethyl acetate, reacted at 65°C for 14 hours, and the product was washed and dried to obtain CNT-PDMS-NH 2 Hybrid.
[0039] Preparation of polyethylene terephthalate composite material: 100 parts of PET resin particles, 2.5 parts of CNT-PDMS-NH 2 A hybrid, a mixture of 3 parts of trimethylolpropane triglycidyl ether and diethylene glycol diglycidyl ether (the mass ratio of the two is 1:1), 3 parts of 1,2,4-benzenetricarboxylic anhydride, and 0.6 parts of N,N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine were added into an internal mixer and reacted at 245°C for 30 minutes with a rotor speed of 35 r / min to obtain a highly wear-resistant PET composite material.
[0040] Example 3
[0041] This embodiment provides a highly wear-resistant polyethylene terephthalate composite material and a preparation method thereof.
[0042] The details are as follows:
[0043] Acylation of carbon nanotubes: 5 parts of carboxylated carbon nanotubes were ultrasonically dispersed in 100 parts of thionyl chloride and refluxed at 90° C. for 20 h to obtain acylated carbon nanotubes.
[0044] Preparation of CNT-PDMS-NH 2 Hybrid: 15 parts of acyl chloride carbon nanotubes, 18 parts of bis-aminopropyl polydimethylsiloxane (and) tridecyl alcohol polyether-10, and 2 parts of triethylamine were uniformly dispersed in 100 parts of carbon tetrachloride, reacted at 85°C for 16 hours, and the product was washed and dried to obtain CNT-PDMS-NH 2 Hybrid.
[0045] Preparation of polyethylene terephthalate composite material: 100 parts of PET resin particles, 5 parts of CNT-PDMS-NH 2 The hybrid, 4 parts of pentaerythritol tetraglycidyl ether, 4 parts of a mixture of 3,3',4,4'-benzophenone tetracarboxylic dianhydride and pyromellitic dianhydride (the mass ratio of the two is 1:1), and 0.3 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] were added into an internal mixer, reacted at 260°C for 25 minutes, and the rotor speed was 40r / min to obtain a highly wear-resistant PET composite material.
[0046] Comparative Example 1
[0047] This comparative example provides a polyethylene terephthalate composite material. Compared with Example 1, Comparative Example 1 does not contain carbon nanotube acyl chloride and preparation of CNT-PDMS-NH 2 The hybrid step, in which in the step of preparing the polyethylene terephthalate composite material, carboxylated carbon nanotubes are used instead of CNT-PDMS-NH 2 The remaining components, preparation steps and parameters of the hybrid are consistent with those in Example 1.
[0048] Comparative Example 2
[0049] This comparative example provides a polyethylene terephthalate composite material. Compared with Example 2, Comparative Example 2 does not contain carbon nanotube acyl chloride and preparation of CNT-PDMS-NH 2 The hybrid step, in which in the step of preparing the polyethylene terephthalate composite material, bisamino PEG / PPG-41 / 3 aminoethyl PG-propyl polydimethylsiloxane is used instead of CNT-PDMS-NH 2 The remaining components, preparation steps and parameters of the hybrid are consistent with those of Example 2.
[0050] Comparative Example 3
[0051] This comparative example provides a polyethylene terephthalate composite material. Compared with Example 2, Comparative Example 3 does not contain carbon nanotube acyl chloride and the preparation of CNT-PDMS-NH 2 The hybrid step, in which in the step of preparing the polyethylene terephthalate composite material, carboxylated carbon nanotubes and bisamino PEG / PPG-41 / 3 aminoethyl PG-propyl polydimethylsiloxane are used instead of CNT-PDMS-NH 2 The weight ratio of the hybrid (carboxylated carbon nanotubes and bisamino PEG / PPG-41 / 3 aminoethyl PG-propyl polydimethylsiloxane) is 1:1, and the sum of the weights of the two is the same as that of CNT-PDMS-NH 2 The other components, preparation steps and parameters are consistent with those in Example 2.
[0052] Comparative Example 4
[0053] This comparative example provides a polyethylene terephthalate composite material. Compared with Example 2, in the step of preparing the polyethylene terephthalate composite material, CNT-PDMS-NH 2 The amount of the hybrid added was 15 parts, and the remaining components, preparation steps and parameters were consistent with those in Example 2.
[0054] Comparative Example 5
[0055] This comparative example provides a polyethylene terephthalate composite material. Compared with Example 3, in the step of preparing the polyethylene terephthalate composite material in Comparative Example 5, pentaerythritol tetraglycidyl ether and the mixture of 3,3',4,4'-benzophenone tetracarboxylic dianhydride and pyromellitic dianhydride are not added, and the remaining components, preparation steps and parameters are consistent with those in Example 3.
[0056] Comparative Example 6
[0057] This comparative example provides a polyethylene terephthalate composite material. Compared with Example 3, in the step of preparing the polyethylene terephthalate composite material in Comparative Example 6, pentaerythritol tetraglycidyl ether is not added, and the remaining components, preparation steps and parameters are consistent with those in Example 3.
[0058] Comparative Example 7
[0059] This comparative example provides a polyethylene terephthalate composite material. Compared with Example 3, in the step of preparing the polyethylene terephthalate composite material, the mixture of 3,3',4,4'-benzophenone tetracarboxylic dianhydride and pyromellitic dianhydride is not added in Comparative Example 7, and the remaining components, preparation steps and parameters are consistent with those in Example 3.
[0060] Comparative Example 8
[0061] This comparative example provides a polyethylene terephthalate composite material. Compared with Example 3, in the step of preparing the polyethylene terephthalate composite material in Comparative Example 8, the amount of pentaerythritol tetraglycidyl ether added is 10 parts, and the other components, preparation steps and parameters are consistent with those in Example 3.
[0062] Comparative Example 9
[0063] This comparative example provides a polyethylene terephthalate composite material. Compared with Example 3, in the step of preparing the polyethylene terephthalate composite material in Comparative Example 9, the added amount of a mixture of 3,3',4,4'-benzophenone tetracarboxylic dianhydride and pyromellitic dianhydride (the mass ratio of the two is 1:1) is 10 parts, and the other components, preparation steps and parameters are consistent with Example 3.
[0064] The PET composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 9 were pressed into specimens, and their wear amount (mass wear) was tested with reference to GB / T3960-2016, and their tensile strength was tested with reference to GB / T 1040.2-2022. The test results are shown in Table 1.
[0065] Table 1 Test results of mass wear and tensile strength of PET composites
[0066] sample Wear amount (g) Tensile strength(MPa) Example 1 0.075 74.26 Example 2 0.044 76.67 Example 3 0.084 73.26 Comparative Example 1 0.221 71.01 Comparative Example 2 0.363 68.79 Comparative Example 3 0.108 73.28 Comparative Example 4 0.041 65.89 Comparative Example 5 0.115 66.72 Comparative Example 6 0.097 65.42 Comparative Example 7 0.105 66.38 Comparative Example 8 0.088 70.08 Comparative Example 9 0.092 69.97
[0067] From the results in Table 1, it can be seen that for Examples 1 to 3, the CNT-PDMS-NH 2 The hybrid is introduced into the PET molecular chain to exert its efficient wear-resistant and self-lubricating effect; at the same time, the efficient chain extension effect of the multifunctional acid anhydride / epoxy compound greatly increases the molecular weight and molecular entanglement degree of PET, obtaining a PET composite material with low wear (0.044~0.084g) and high tensile strength (73.26~76.67MPa).
[0068] Comparative Example 1: Using carboxylated carbon nanotubes instead of CNT-PDMS-NH 2 Hybrid, due to the poor dispersion of carbon nanotubes in the PET matrix, the wear resistance and mechanical properties of the obtained composite material are relatively low, the wear loss increases to 0.221g, and the tensile strength decreases to 71.01MPa.
[0069] For Comparative Example 2, the wear loss of the obtained composite material increased significantly to 0.363 g, and the tensile strength was 68.79 MPa, indicating that the anti-wear performance of PET cannot be improved by bisamino PEG / PPG-41 / 3 aminoethyl PG-propyl polydimethylsiloxane alone.
[0070] In Comparative Example 3, carboxylated carbon nanotubes and bisamino PEG / PPG-41 / 3 aminoethyl PG-propyl polydimethylsiloxane were simply compounded and then melt-blended with PET resin to obtain a composite material. Due to the weak interfacial interaction between the two and PET, it is difficult to fully exert the wear-resistant self-lubricating effect, and the wear loss of the composite material is 0.108g.
[0071] For Comparative Example 4, although Examples 1 to 3 confirm that adding CNT-PDMS-NH 2 Hybrids can improve the wear properties of PET, but adding excessive amounts of CNT-PDMS-NH 2 Hybrids will result in CNT-PDMS-NH 2 The hybrids were difficult to disperse evenly in the PET matrix and a large number of agglomerates occurred, which ultimately significantly reduced the tensile strength of the composite material, while its wear loss remained at a low value. 2 The amount of the hybrid added is preferably 0.1 to 5 parts by weight, preferably 2 to 5 parts by weight.
[0072] For Comparative Example 5, CNT-PDMS-NH 2 Good dispersion of the hybrid in PET helps to improve the wear resistance, but the composite material does not contain polyfunctional anhydride compounds and polyfunctional epoxy compounds, the molecular entanglement of the system is low, its wear loss is 0.115g, and the tensile strength is only 66.72MPa.
[0073] For Comparative Examples 6 and 7, no multifunctional epoxy compound or multifunctional anhydride compound is added to the composite material, the molecular entanglement density of the system is low, the tensile strength of the composite material is significantly reduced, and the wear amount is increased compared with Example 3.
[0074] For comparative examples 8 and 9, it is difficult for the excessive multifunctional epoxy compound or multifunctional acid anhydride compound to completely react with the active end groups of PET, and remain in the PET matrix as small molecular substances, resulting in increased wear of the composite material and reduced tensile strength. The dosage ratio of the multifunctional epoxy compound to the multifunctional acid anhydride compound is more suitable at 0.5 to 1:1, and 1:1 is the best.
[0075] In summary, the highly wear-resistant polyethylene terephthalate composite material provided by the present invention comprises a polyfunctional epoxy compound, a polyfunctional acid anhydride compound and a CNT-PDMS-NH 2 Under the joint action of hybrids and other raw materials, the PET matrix is modified, and the obtained polyethylene terephthalate composite material has excellent wear resistance and mechanical properties, and can adapt to the requirements of harsh working conditions.
[0076] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0077] The above is a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A highly wear-resistant polyethylene terephthalate composite material, characterized in that: The invention comprises the following components in parts by weight: 100 parts of PET resin, 0.1 to 5 parts of CNT-PDMS-NH2 hybrid, 0.05 to 5 parts of multifunctional epoxy compound, 0.05 to 5 parts of multifunctional acid anhydride compound and 0.01 to 3 parts of antioxidant; the CNT-PDMS-NH2 hybrid is obtained by reacting carbon nanotubes with amino-terminated polydimethylsiloxane.
2. The highly wear-resistant polyethylene terephthalate composite material according to claim 1, characterized in that: The preparation method of the CNT-PDMS-NH2 hybrid is as follows: 1 to 20 parts by weight of acyl chloride carbon nanotubes, 1 to 20 parts by weight of a bisamino polydimethylsiloxane mixed compound, and 0.5 to 5 parts by weight of triethylamine are uniformly dispersed in 100 parts of a solvent, reacted at 35 to 100° C. for 5 to 20 hours, and the product is washed and dried to obtain a CNT-PDMS-NH2 hybrid.
3. The highly wear-resistant polyethylene terephthalate composite material according to claim 2, characterized in that: The preparation method of the acyl chloride carbon nanotubes is as follows: 0.4-5 parts by weight of carboxyl carbon nanotubes are ultrasonically dispersed in 100 parts of thionyl chloride, and refluxed at 60-90° C. for 10-20 hours to obtain acyl chloride carbon nanotubes.
4. The highly wear-resistant polyethylene terephthalate composite material according to claim 2, characterized in that: The bis-amino dimethicone compound is selected from one or more of bis-aminopropyl dimethicone, bis-amino PEG / PPG-41 / 3 aminoethyl PG-propyl dimethicone, dual-terminated amino dimethicone (and) octylphenol polyether-40 (and) isolauryl alcohol, bis-aminopropyl dimethicone (and) trideceth-10, dual-terminated amino dimethicone (and) trideceth-10 (and) stearyl.
5. The highly wear-resistant polyethylene terephthalate composite material according to claim 2, characterized in that: The solvent is selected from at least one of n-hexane, petroleum ether, chloroform, carbon tetrachloride, benzene, toluene and ethyl acetate.
6. The highly wear-resistant polyethylene terephthalate composite material according to claim 1, characterized in that: The multifunctional epoxy compound is selected from one or more of ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, pentaerythritol tetraglycidyl ether, bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether, resorcinol diglycidyl ether, trimethylolpropane triglycidyl ether, glycerol triglycidyl ether, 1,4-butanediol diglycidyl ether, and castor oil triglycidyl ether.
7. The highly wear-resistant polyethylene terephthalate composite material according to claim 1, characterized in that: The multifunctional acid anhydride compound is selected from one or more of pyromellitic anhydride, biphenyltetracarboxylic anhydride, pyromellitic anhydride, maleic anhydride, 1,2,4-tricarboxylic anhydride, 4,4'-oxydiphthalic anhydride, 3,3',4,4'-diphenyl ether tetracarboxylic anhydride, 3,3',4,4'-benzophenone tetracarboxylic anhydride and 3,4,9,10-tetracarboxylic anhydride.
8. The highly wear-resistant polyethylene terephthalate composite material according to claim 1, characterized in that: The antioxidant is selected from β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], di-tert-butyl-p-cresol, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanuric acid, N,N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl] hydrazine, bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite, 4,4'-methylenebis(2,6-di-tert-butylphenol) propionate, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanuric acid, N,N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl] hydrazine, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl] hydrazine ... One or more of tert-butylphenol, 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, 2,6-di-tert-butyl-4-(dimethylaminomethyl)phenol, tris[2,4-di-tert-butylphenyl]phosphite, N,N'-bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hexanediamine, 2,6-di-tert-butyl-4-methylphenol and triethylene glycol bis-3-(3-tert-butyl-4-hydroxy-5-methylbenzyl)propionate.
9. The highly wear-resistant polyethylene terephthalate composite material according to any one of claims 1 to 8, characterized in that: The wear loss of the highly wear-resistant polyethylene terephthalate composite material is less than 0.090 g, and the tensile strength exceeds 72.00 MPa.
10. A method for preparing a highly wear-resistant polyethylene terephthalate composite material, characterized in that: The following steps are involved: 100 parts by weight of PET resin, 0.1 to 5 parts by weight of CNT-PDMS-NH2 hybrid, 0.05 to 5 parts of multifunctional epoxy compound, 0.05 to 5 parts of multifunctional acid anhydride compound, and 0.01 to 3 parts of antioxidant are added into an internal mixer, and reacted at 230 to 260° C. for 10 to 50 minutes at a rotor speed of 10 to 50 r / min to obtain a highly wear-resistant PET composite material; The CNT-PDMS-NH2 hybrid is obtained by reacting carbon nanotubes with amino-terminated polydimethylsiloxane.
Citation Information
Patent Citations
PET (Polyethylene Terephthalate) composite material with wear-resistant effect and application of PET composite material in packaging material
CN116554654A
A high-strength wear-resistant PET material and preparation method thereof
CN118256071B